Desenvolvimento de metodologias sustentáveis para a síntese de tetraidroquinolinas: o uso de hemiacetais como indutores de assimetria - Quaglio, Karina de Souza (Universidade Federal de São Carlos, 2021)
Heterocyclic compounds constitute the most important class of organic compounds today, being present in pharmaceutical compounds, natural products, vitamins, and presenting different biological activities. In particular, N-heterocycles are present in 59% of drugs approved by the FDA (Food and Drug Administration). In this context, tetrahydroquinolines (THQ) have been highlighted due to their vast presence in natural products with biological activity and in pharmacologically relevant therapeutic agents, which is why the development of new synthesis methodologies for this class of compounds is a research target of interest. Inspired by literature reports and by the existing gap in obtaining THQs with high structural diversity and stereochemical control, this master's project aims to develop a protocol to synthesize diasteromerically enriched and highly diverse 1,2,3,4-tetrahydroquinoline derivatives through an organocatalyzed Michael addition followed by an Ugi-Smiles reaction. Therefore the objective is to synthesize a substrate with two of the functional groups of the Ugi reaction, aiming to control the diastereoselectivity of Ugi-4C-3CR through an intramolecular approach.
Development of sustainable methodologies for the synthesis of tetrahyroquinolines: the use of hemiacetals as asymmetry inductors
Keywords: Tetraidroquinolinas; Organocatálise; Adição de Michael; Reação multicomponente; Reação de Ugi-Smiles; Tetrahydroquinolines; Organocatalysis; Michael addition; Multicomponent reactions; Ugi-Smiles reaction; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::SINTESE ORGANICA